WORK STRESS ON EMPLOYEES PERFORMANCE OF PT ANGKASA PURA KARGO BANTEN WITH WORK ENVIRONMENT AS A MEDIATING VARIABLE - Peter Rajagukguk; Nurhadi Nurhadi; Dedi Supriadi; Hardani Hardani (Sean Institute, 2023)
Modern technological development in industry has done a lot of good in helping to complete a job, Can improve the performance of an employee. This research aims to determine the effect of work stress and the work environment on employee performance in the regulated agent division of PT Angkasa Pura Kargo. This type of research is quantitative statistics using smartpls4, with outer measurements models and inner models. The method of data collection using the questionnaires distributed online to 100 employees on the Regulated Agent division as respondents, using a saturated sampling technique. The results of this research show that the calculated T value > T table and P Values ​​< 0.05 means that partially work stress has a significant effect on employee performance, the work environment has a significant effect on employee performance, work stress has a significant effect on the work environment. Simultaneously, work stress and the work environment influence employee performance with an R Square of 0.837. or 83.7%. belongs to the strong category.